2019
DOI: 10.1021/acs.iecr.9b01344
|View full text |Cite
|
Sign up to set email alerts
|

Two-Fluid-Model-Based Full Physics Simulations of Mixing in Noncohesive Wet Fluidized Beds

Abstract: Mixing in a noncohesive wet fluidized bed was studied using the two-fluid model (TFM) and a zero-dimensional (0D) approach. The employed TFM was extended to simulate droplet deposition on the particles, droplet evaporation, and particle drying. To quantify the bed uniformity, the variance of temperature and the particles’ loss on drying (LoD) field were computed. Subsequently, our TFM simulation data is used to support the assumptions adopted in our 0D model. Specifically, the simulation results suggest the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The only exception is when the bed falls into the bubble-less expansion regime. This finding is in accordance with our previous study and the study of Luding and Radl et al . This revealed that particle cohesiveness increases the velocity fluctuation at the particle level.…”
Section: Resultssupporting
confidence: 94%
“…The only exception is when the bed falls into the bubble-less expansion regime. This finding is in accordance with our previous study and the study of Luding and Radl et al . This revealed that particle cohesiveness increases the velocity fluctuation at the particle level.…”
Section: Resultssupporting
confidence: 94%
“…Using the least squares method, α coh, 1 for the best fitting is shown to decrease (from 785 to 682) with the increase of B o (see the legend of Figure ). This may be ascribed to the decreased particle velocity for the increase of B o in fluidization of particles; for the particles with decreased velocity and increased B o , they may have more enduring contacts with their neighbors, which may more easily lead to the negative tensile pressure and result in a smaller α coh, 1 .…”
Section: Resultsmentioning
confidence: 99%
“…These facts motivated our study in rectangular beds that are significantly easier to analyze both experiments and simulations. Besides, the validation study conducted in our previous work 41 demonstrated the reliability of 2D TFM for cylindrical FB in the range of u < 4 u mf .…”
Section: Mathematical Modelmentioning
confidence: 78%
“…To calculate the sample means, the mass fraction x s in each cell was weighted with the cell's solid volume fraction. Readers are referred to our previous work 41 for more information about the encoded modules for sampling procedure. The resulting time history of scalar variance is stored in the disk.…”
Section: Resultsmentioning
confidence: 99%